The ship in the sky - Evans, Tracey Ellen (Department of English Language and Literature, 2020)
The sky’s grumbling. Layers of gray grinding above me the way teeth grind, angry and wanting, all nap long. Two boom-clap bangs and my eyes snap open to clouds thick as clay, metal-sheet lightening and thunder thumping close and heavy as fists. I grab the stone floor and I’m watching and listening, listening and watching and I’m hearing yelling and it’s my own heart yelling, and I realize this ain’t dreaming. This ain’t dreaming. I ease myself near the rock ledge, hanging there like a loose tooth when the ground rips apart, it clear splits thirty feet in front of me right through the Joneses' veggie patch. My gut leaps to my throat. Would be an awesome sight if it weren’t so terrifying. Air and water and fire and earth dancing into one, blasting the ground inches from the Joneses’ farmhouse splitting their flagpole, my eardrums just about splitting in the roar. I clasp on tight. Next thing, my legs are falling from my body, or my body’s falling from the rock and we’re sinking together, sliding down. Then silence. Earth shattering silence. A venomous pause. Nothing moves, not even my lungs. I grab at the ledge hanging, waiting, watching. Come on Bill. Get out of the house. Get the Missus and get the fuck out. The elements are hovering, brewing a soup so thick and dark a rich thick and dark soup. Triple decker boom and I’m rolling to the spine of the rock as it tilts and digs its feet in, crushing or protecting, as the sky breaks open with rain belting down. I crank my head towards the farmhouse and it’s sinking. Come on Bill and Betty. As the sky belts the earth belts my skull belts on the back of that blasted crushing protecting rock, the ground sinking further under the weight from above and rock falling, consciousness too, and then I’m dreaming of everything.